2015
DOI: 10.5539/gjhs.v8n5p184
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Maternal Periodontal Status of and Preterm and Low Birth Weight Infants in Iran: A Case Control Study

Abstract: Aim and Background:It has been suggested that periodontitis is associated with systemic alterations such as adverse pregnancy outcomes. However, some conflicting results have been reported. This study was conducted to determine the association between periodontitis and preterm birth (PTB), low birth weight (LBW) to obtain information which is necessary for the planning of preventive programs of periodontal disease for pregnant women in this area.Materials & Methods:This case-control study was performed on 264 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
0
15
0
14
Order By: Relevance
“…The association between CP and LBW was rst reported by Offenbacher et al [1]. Many epidemiological studies have reported that pregnant women with CP are several times more likely than women without CP to have a preterm LBW infant [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Additionally, some studies have found that treatment for periodontitis is effective for preventing LBW [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between CP and LBW was rst reported by Offenbacher et al [1]. Many epidemiological studies have reported that pregnant women with CP are several times more likely than women without CP to have a preterm LBW infant [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Additionally, some studies have found that treatment for periodontitis is effective for preventing LBW [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic bacterium of CP and chemical mediators produced by in ammation in gingiva were considered to penetrate into weak capillary blood vessels, and then to cord blood through the placenta [2][3][4]. Some researchers have reported that CP in uences the development of LBW [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], whereas others have denied such an association [23][24][25][26][27]. Therefore, no consensus has been reached on the association between CP and LBW [28][29][30][31], and more studies are needed to address this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Poor oral health in pregnant women has shown associations with the risk of adverse pregnancy outcomes (4,5), and increases the chance of dental caries in their children (6). Pregnant women's regular tooth brushing and dental attendances are reported to be undesirable worldwide (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…1 It is estimated that the majority of pregnant women experience gingivitis resulting from pregnancy-related hormonal changes. 3,13,28 Various studies have identified a large range regarding the prevalence of pregnancy gingivitis, from 36% in one study to 100% in another. 3,13,28 Differences in study design and demographics of study participants may account for these considerable variations.…”
mentioning
confidence: 99%
“…3,13,28 Various studies have identified a large range regarding the prevalence of pregnancy gingivitis, from 36% in one study to 100% in another. 3,13,28 Differences in study design and demographics of study participants may account for these considerable variations. Periodontitis, an inflammatory disease of the periodontal tissues, is the advanced stage of gingival disease, involving inflammation and destruction of the supporting structures of the teeth.…”
mentioning
confidence: 99%